Idiopathic chronic productive cough and response to open‐label macrolide therapy: An observational study. Issue 6 (5th February 2019) - Martin, Matthew J.; Lee, Helen; Clayton, Carly; Pointon, Kate; Soomro, Irshad; Shaw, Dominick E.; Harrison, Tim W.
Abstract: Background and objective: Adult patients with chronic productive cough of unknown cause are commonly seen in respiratory clinics. We have previously described a subgroup of these patients who have a short‐lived response to standard antibiotic treatment but a prolonged response to 3 months of low‐dose azithromycin therapy. Methods: This observational study describes the physiological, radiological and pathological features of this patient cohort along with their response to a 12‐week open‐label trial of 250 mg azithromycin thrice weekly. Results: A total of 30 subjects with a mean age of 57 were recruited. The majority demonstrated airway dilatation on high‐resolution computed tomography (HRCT) scan without evidence of established bronchiectasis ( n = 21) and non‐specific chronic inflammatory changes on bronchial biopsy ( n = 15/17). Twenty‐nine subjects completed 3 months of azithromycin with a significant improvement in median Leicester Cough Questionnaire (LCQ) score (−6.3 points, P < 0.00001), reduction in median 24‐h sputum volume (−5.8 mL, P = 0.0003) and improvement in sputum colour ( P = 0.003). Patients responsive to azithromycin ( n = 22) demonstrated neutrophilic or paucigranulocytic airway inflammation, whereas five subjects with eosinophilic airways inflammation did not respond symptomatically to azithromycin. Conclusion: We describe a cohort of patients with chronic productive cough not adequately described by existing disease labels whose symptoms responded well to low‐dose azithromycin. Many of the features are similar to the paediatric condition protracted bacterial bronchitis. Abstract : A group of patients with chronic productive cough of unknown cause not adequately described by existing disease labels is described in terms of their physiological, radiological and pathological features. The majority of these patients demonstrated neutrophilic or paucigranulocytic airway inflammation and their symptoms responded well to azithromycin. See related  Editorial